LA FLAUTA DE PAN DEL SACERDOTE GUERRERO DE SIPAN EN (DE) LA ALTA JERARQUIA MOCHICA - Sánchez Huaringa, Carlos D. (2015)
In 2007, the archaeologist Luis Chero Zurita discovers the tomb number 14 of the “Warrior Priest” of Sipan Moche belonging to the elite, and their grave goods is twenty sound artifacts (pututos and horns) and musical instruments (flutes bread or “antaras”). From the perspective of research proposal, developed in this article an exploration of various tonnage musicological aspects of the panpipes and its relationship with the character mentioned, raising questions and clues for future research needed.